Determining Factors of Energy Intensity in the Manufacturing Industry of Provinces in Indonesia - Peggy Hariwan; Feri Sunaryo; Muhammad Kholil (Universitas Islam Riau (UIR) Press, 2022)
Energy is vital to Indonesia's economic activities in various sectors. Energy plays an important role in the sustainability of the economic structure, which includes is the manufacturing industry. However, limited natural resources are one of the challenges for policymakers. Although energy conservation policies have been implemented in Indonesia since 1982, their enforcement in the manufacturing industry sector has not been solutive in supporting the development of the manufacturing industry in all regions. This study aims to determine the relationship between the development of energy intensity and economic growth in 26 provinces of Indonesia, using the growth and share analysis method from the data the authors have obtained. The results showed that the paper and printed goods, cement, and non-metallic minerals industries are the sub-sectors with high energy consumption. Then, Riau, DKI Jakarta, and West Java provinces are in the dominant quadrant for economic growth, but their energy intensity is in the low/slow quadrant. This indicates that industries in these three provinces have efficient use of energy.